(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
Information resources are required for the adequate performance of parliamentary functions. There are multiple and varied sources and ways in which this information arrives and moves in parliaments. Among them we may distinguish the parliamentary investigation services. This paper seeks, firstly, to identify and reflect on the specific information needs of the parliamentary institutions to which these services must respond, analysing some of the main studies dedicated to the subject in the last decades. Secondly, it identifies some features that may be used to characterise parliamentary research services and the products they develop, as well as to distinguish them from other information providers, with particular attention to accuracy, relevance and trustworthiness; independence, impartiality and neutrality; and conciseness, easy and fast access and proper adaptation to the needs and characteristics of parliamentarians. Finally, the main products and services they usually provide are pointed out.